A network analysis of postpartum depression and mother-to-infant bonding shows common and unique symptom-level connections across three postpartum periods - Norihiro Harasawa; Chong Chen; Sumiyo Okawa; Ryo Okubo; Toshio Matsubara; Shin Nakagawa; Takahiro Tabuchi (Communications Psychology)
Abstract Postpartum depression and mother-to-infant bonding difficulties (MIBD), two issues crucial to maternal and infant mental health, often coexist and affect each other. Our study aims to dissect their complex relationship through a graphical LASSO network analysis of individual symptoms in 5594 Japanese postpartum women, whose geographical distribution was nationally representative. We identified ‘fear’, ‘enjoyment’, ‘overwhelm’, and ‘insomnia’ as common bridge symptoms linking postpartum depression and MIBD across three distinct postpartum periods. Moreover, ‘self-harm’ emerged as a bridge symptom in the first 6 months and the 7–12 month period, while ‘laugh’ was a bridge symptom in the first 6 months and the 13–24 month period. Notably, ‘self-blame’ was identified as a unique bridge symptom specific to the 13–24 month period. Our analysis highlights the complexities of symptom connectivity across postpartum stages and underscores the critical need for interventions that address both common and stage-specific bridge symptoms to effectively support maternal mental health and strengthen mother-to-infant bonding.